Effect of Current Ratio, Debt to Equity Ratio, Return on Equity Ratio, and Net Profit Margin Ratio on Financial Distress Conditions in Hotel, Restaurant, and Tourism Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2017–2020 Period - Musa Panjaitan; Putri Naulina Br Sagala; Hanna Melkyana Napitupulu; Janfrina Paramitha Mayawi Br Tarigan T; Ferdinand Napitupulu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to determine and analyze effect of current ratio, debt to equity ratio, return on equity ratio, and net profit margin ratio on financial distress conditions in Hotel, Restaurant, and Tourism Sub-Sector Companies listed on the Indonesia Stock Exchange for the 2017–2020 period. This research is descriptive and quantitative. The population in this study in Hotel, Restaurant, and Tourism Sub-Sector Companies listed on the Indonesia Stock Exchange for the 2017–2020 period totaling 35 companies. The number of research samples is 21 x 4 is 84 samples. The data analysis method is multiple linear regression. The results of the research using partial test (t) is that current ratio has a positive and no significant effect on financial distress conditions. Debt to equity ratio has a positive and significant effect on financial distress conditions. Return on equity ratio has a negative and significant effect on financial distress conditions. Net profit margin ratio has a positive and no significant effect on financial distress conditions. In simultaneous test (F) is current ratio, debt to equity ratio, return on equity ratio, and net profit margin ratio have a significant effect simultaneously on financial distress conditions.